Can Engineered "Designer" T Cells Outsmart Chronic Hepatitis B?. (1st August 2010) - Protzer, U.; Abken, H.
Abstract : More than 350 million people worldwide are persistently infected with human heptatitis B virus (HBV) and at risk to develop liver cirrhosis and hepatocellular carcinoma making long-term treatment necessary. While a vaccine is available and new antiviral drugs are being developed, elimination of persistently infected cells is still a major issue. Recent efforts in adoptive cell therapy are experimentally exploring immunotherapeutic elimination of HBV-infected cells by means of a biological attack with genetically engineered "designer" T cells.